The Popularity of K-Pop Culture in Russia: Good or Evil? The Case of BTS - M. A. Kashina (Управленческое консультирование, 2023)
The export and consumption of mass culture products through social networks is practically uncontrollable through globalization. The Republic of Korea, which has made a bet on its creative industries, has achieved noticeable success in this area. The number of fans of the Korean wave (Hallyu) is growing all over the world, in Russia too. K-pop, the musical component of Hallyu, is the most interesting because most of its fans are young people. This actualizes the question about consequences of the k-pop passion on the individual and societal levels.   The purpose of the study: to analyze the causes and consequences of Russians’ passion for k-pop, in particular, the BTS creativity.   The theoretical basis is the theory of the cultural industry by M. Horkheimer — T. Adorno and the theory of social media by M. McLuhan — G. Jenkins. The online fandom BTS — ARMY is seen as an informal social institution of mass culture.   Empirical base. Online survey of Russian BTS fans (N=2483), 13 personal fan essays, 5 focus groups with people of different ages who are not fans but know them well. results.    Results. The passion for k-pop, in particular BTS, is a form of response to the challenges of modern society, in particular, the growth of loneliness, competition, the devaluation of moral values and the crisis of family relations. Positive effects are associated with the personal development of fans, broadening their horizons, increasing self-confidence and tolerance, the emergence of new forms of leisure and hobbies. Participation in a fandom creates a sense of group identity and solidarity, and social networks allow the development of a “culture of participation”. Negative effects are manifested in the idealization of South Korea, its people and culture, the desire to remain in the “beautiful fairy tale” created by the South Korean cultural industries. As a result, groups of female fans are self-isolating. Considering an idol, far from Russian realities, as a normative model of a man, leads to difficulties in building partnerships between female fans with the opposite sex. Non-aggressive behavior of ARMY forms a generally tolerant attitude towards them. K-pop fandom is perceived as a childhood disease that will eventually go away without much treatment. According to opinion of focus group participants, it does not pose a threat to national security and the national identity of the inhabitants of Russia. directions for further research are related to a more detailed analysis of the mechanisms of BTS psychological support for their fans, a comparison of the socio-demographic composition and main types of activity of Russian fans of male and female K-pop groups, an assessment of the meaning of the “complicity culture”, which BTS fans create, for their personal development.